2021
DOI: 10.1155/2021/8871166
|View full text |Cite
|
Sign up to set email alerts
|

A Gas Sensor for Application as a Propane Leak Detector

Abstract: A propane gas detector was built based on the semiconductor nickel antimonate oxide (NiSb2O6) by means of an analog electronic circuit. The gas detector was designed for monitoring atmospheres where the leakage of propane gas could possibly occur. The prototype’s construction methodology is presented in 5 stages: (1) synthesis of NiSb2O6 oxide powders, (2) characterization of the powders by XRD and TEM, (3) manufacture and electrical characterization of the chemical gas sensor, (4) design of the analog circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Therefore, we consider that the ZnAl 2 O 4 is a strong candidate to be applied as a sensor of toxic gases, mainly propane. Comparing the results in Figure 2 with those reported in the references [9,15,23], we found that our sensor ZnAl 2 O 4 had better sensitivity, excellent dynamic response, good reproducibility, shorter response and recovery times at 250 • C. In addition, the curves obtained from the experiments performed at 1000-ppm propane concentrations (see Figure 2), were consistent with those reported in reference [1].…”
Section: Analysis Of the Dynamic Response Of The Znal 2 Osupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, we consider that the ZnAl 2 O 4 is a strong candidate to be applied as a sensor of toxic gases, mainly propane. Comparing the results in Figure 2 with those reported in the references [9,15,23], we found that our sensor ZnAl 2 O 4 had better sensitivity, excellent dynamic response, good reproducibility, shorter response and recovery times at 250 • C. In addition, the curves obtained from the experiments performed at 1000-ppm propane concentrations (see Figure 2), were consistent with those reported in reference [1].…”
Section: Analysis Of the Dynamic Response Of The Znal 2 Osupporting
confidence: 89%
“…That was repeated on several occasions (cycles), which indicated that the pellets maintained a stable process of reversibility and stability in air-propane atmospheres [1]. The excellent response of the ZnAl 2 O 4 was attributed mainly to the reaction that took place on the pellets' surface between the oxygen and the test gas because of the operating temperature (250 • C) [15,23,24]. The temperature provoked the activation of the charge carriers (electrons) [1], making them move faster on the sensor's surface [23,25], causing an almost immediate change in electrical resistance and an increase in the sensitivity of the pellets [1].…”
Section: Analysis Of the Dynamic Response Of The Znal 2 Omentioning
confidence: 96%
See 1 more Smart Citation
“…Effective air pollution prevention and control measures are required when designing ventilation systems [36]. The results obtained from this study predict the nature of LPG dispersion from the chosen source (illegal car parked in an underground garage equipped with LPG installation), which plays a crucial role in the estimation of proper places for the sensors [37].…”
Section: Jet Ventilationmentioning
confidence: 88%
“…The electrical response of these semiconductors is based on the adsorption and desorption of oxygen ions on the surface [3,4] and the mobility of the charge carriers (holes or electrons) due to the temperature employed in the tests [1][2][3][4][5][6]. The variation in the electrical signal (resistance) shown by the semiconductor oxides depends on the detected gas and the type of semiconductor (p or n) [6,7]. In the gas sensor field, n-type semiconductors are the most studied [8] because they show excellent electrical response, thermal stability, and efficiency toward almost any gas (CO, O 2 , CO 2 , SO 2 , CH 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%